From Colony to Nation: The Growth of Science and Biology Education in Singapore (1959–1978) - Vinodhen, Vanessa (Southeast Asia Development Research, 2025)
This research presents a comprehensive historical analysis of Singapore's educational transformation from 1959 to 1978, focusing on the development of science and biology education during that time. The intricate relationships between post-colonial nation-building, economic imperatives, and educational reform are examined. Through a multi-theoretical lens incorporating institutional theory, post-colonial theory, and human capital development frameworks, this study investigates how Singapore's education system, particularly science and biology educaiton evolved during its critical survival-driven phase. The research employs an enhanced qualitative historical methodology, combining traditional archival analysis with comparative historical analysis and policy trajectory studies. Drawing upon previously underutilized archival materials, government documents, and oral histories, this study reveals how Singapore's educational policies were strategically crafted to address both immediate survival needs and long-term development goals. The findings demonstrate that Singapore's emphasis on science and biology education was not merely a response to economic demands but represented a sophisticated strategy integrating national identity formation, economic development, and social cohesion. This research contributes to our understanding of how post-colonial nations can leverage educational policy as a tool for both economic development and social transformation, offering valuable insights for contemporary education policymakers in developing nations.